Personalized Medicine in Patients with Colo-rectal Liver Metastases - Mohammadhossein Hooshangi; Aynaz Nouri; Fatemeh Soleymani Lashkenari (Tehran University of Medical Sciences, 2023)
Background The precision Medicine initiative is a new research exertion intending to offer personalized medicine in many illnesses, including cancer. The purpose of the current article is to offer novel insights about the role of personalized medicine in patients with colorectal liver metastases (CRLM). Experimental An assess the writing in regards to personalized medication and cancer in patient with colorectal liver metastases was performed in the MEDLINE/PubMed database. Result and discussion Surgical resection remains the main hope for a cure of CRLM. Worked on surgical scheme to improve remnant liver volume are as of late presented and making progress. Following resection of CRLM scoring methods have been evolved by amalgamated certain preoperative factors, for example, microsatellite instability KRAS expression and sensitivity to immunotherapy with programmed Death-1 inhibitor. conclusion Multidisciplinary management of patients with CRLM has particularly added to survival. While the most recent quite a few years have been described by these significant developments, future advances for patients with CRLM will rely upon a superior comprehension of genomics and molecular biology to promote with the portrayal of a specific tumor "identity" so that individualized therapy for each CRLM patient turns into the rule, and not the exception.